The Role of Parental Psychology in the Formation of a Particular Religious Beliefs in A Child (Eurasian Scientific Herald, 2023)
In this article, the significance of the psychology of the father-mother personality in the formation of a certain belief in the child was explained based on the theories of foreign and Islamic psychology. Also, research was conducted to determine the scientific basis of these theories